Veterinary care of free‐living hedgehogs. Issue 9 (1st November 2019) - Bexton, Steve; Couper, David
Abstract : Background: Hedgehogs ( Erinaceus europaeus ) are widespread throughout mainland Britain, often inhabiting parks and gardens in built‐up areas. They are popular with the public, frequently coming top in polls of Britain's favourite wild mammal. They are also the most common species of wildlife casualty encountered in veterinary practice. Aim of the article: This article describes the principles of hedgehog care while at the veterinary practice, and the treatment of some of the most common problems.